The most important points in grand slam singles tennis - O'Donoghue, P. G. (Research Quarterly for Exercise and Sport, 2001)
A computerized data management system was used to enter details of points played in 252 tennis matches from the men's and women's singles events of all four Grand Slam tournaments over a 2-year period. A supplementary data analysis system was developed to determine the proportion of points won by each player on serve at each game score from love all to deuce as well as the proportion of games the player went on to win from each score. Analysis of the 43 matches in which both players served at each score from love all to deuce revealed that the proportion of points won by the server was not significantly influenced by score, F(15, 495) = 0.8, p > .05. A further analysis of the 175 matches consisting of at least 100 points revealed that the proportion of points won by the superior player was not significantly influenced by gender, F(1, 165) = 0.1, p > .05, or surface, F(3, 165) = 0.1, p > .05. However, the proportion of points won when serving was significantly greater in men's singles than women's singles, F(1, 165) = 69.7, p < .001, R2 = .30. Surface also had a significant influence on the proportion of points won when serving, F(3, 165) = 8.1, p < .001, R2 = .13, with a significantly greater proportion of points won when serving by both winning and losing players at Wimbledon than at the Australian and French Opens, p < .05. This suggests that gender and surface should be accounted for when determining the importance of points in Grand Slam tennis.